A Critique of Behavioral Psychotherapy: the Groundwork for an Integrated Model of Intervention - Wright, John (Canadian Journal of Counselling and Psychotherapy, 2011)
Several strengths and weaknesses of the behavioral approach in psychotherapy are discussed. Possible remediation of some of the weaknesses are explored through integration of contributions from client-centered or psychodynamic approaches. Finally some of the risks associated with an integrated model of psychotherapy are considered.